PENERAPAN METODE WEIGHTED PRODUCT (WP) PADA PEMILIHAN SISWA PENERIMA BANTUAN MISKIN SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 2 PALU - Wirdayanti, Wirdayanti; A. Masse, Burhannudin; Mufthi, Mufthi (Fakultas Teknik, Universitas Tadulako, 2019)
The goal of this research is to assist teachers and headmaster to selection student who is truly receiving aid poor from the government to consider determined criteria. The technique of data collection is observation, interview and literature. Using the waterfall method for software development methods. This application uses Delphi 2010 and MySQL for CASE Tools and black-box method for testing the function. Application of students selection who are aid poor can display ranking the student who receives aid poor based on the output of Weighted Product methods.